Stigmatized Neighborhoods, Social Bonding, and Health. (8th September 2014) - Wutich, Amber; Ruth, Alissa; Brewis, Alexandra; Boone, Christopher
<x xml:space="preserve">Abstract</x> The relationship between living in impoverished neighborhoods and poor health is well established, but impacts of neighborhood stigma on health are not well understood. Drawing on long‐term research with Latino immigrants, we examine how neighborhood stigma and social bonding affect health in Phoenix, Arizona. During preliminary ethnographic analysis, we developed a novel neighborhood stigma scale. In survey research, we examined effects of neighborhood stigma and social bonding on self‐reported physical and mental health. Regression models show that perceived neighborhood stigma and low social bonding are associated with poorer physical and mental health, controlling for other factors.